Dynamics of Retail‐Bank Branching in Austria. (3rd May 2017) - Burgstaller, Johann
Abstract : This paper examines branch exit from and entry into local banking markets in Austria from 1999 to 2012, as well as changes in concentration and several bank–borrower distance measures. Results from spatial regression models reveal that especially less developed and functionally distant municipalities suffer from branch withdrawal and financial desertification. Bank variety, and thus, choice decreases, for example, in (the vicinity of) communities with ageing population. Most examined processes are found to exhibit spatial correlation and so being geographically extensive. Potential adverse consequences of structural change for non‐urban markets should, thus, receive more attention from economic and regional policy.